2020
DOI: 10.1136/bmjopen-2019-030424
|View full text |Cite
|
Sign up to set email alerts
|

Problem and non-problem gamblers: a cross-sectional clustering study by gambling characteristics

Abstract: ObjectivesGambling characteristics are factors that could influence problem gambling development. The aim of this study was to identify a typology of gamblers to frame risky behaviour based on gambling characteristics (age of initiation/of problem gambling, type of gambling: pure chance/chance with pseudoskills/chance with elements of skill, gambling online/offline, amount wagered monthly) and to investigate clinical factors associated with these different profiles in a large representative sample of gamblers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 61 publications
(91 reference statements)
1
16
0
Order By: Relevance
“…The comparison of the mean age of our sample with previous studies, not only in Australian samples (Russell, Hing, & Browne, 2019), but also in previous samples from our hospital (Jim enez-Murcia et al, 2020), shows that the current sample shows a mean age younger than previous studies (a difference of at least 10 years), so the current sample is in a lower age range compared to previous studies, with a short average disease duration. In this sense, online gambling has been associated with a shorter disease course (Hubert & Griffiths, 2018;Landreat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the mean age of our sample with previous studies, not only in Australian samples (Russell, Hing, & Browne, 2019), but also in previous samples from our hospital (Jim enez-Murcia et al, 2020), shows that the current sample shows a mean age younger than previous studies (a difference of at least 10 years), so the current sample is in a lower age range compared to previous studies, with a short average disease duration. In this sense, online gambling has been associated with a shorter disease course (Hubert & Griffiths, 2018;Landreat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example in the United Kingdom, 38% of the 16 to 24-year-olds gambled in 2016 compared to 5% the previous year (85). In other reports, ∼60-80% of young people engaged in formal or informal gambling before the legal age (11,86,87). This population is at higher risk of losing control compared to older adults, and the prevalence of problem gambling is higher.…”
Section: Younger Targetsmentioning
confidence: 92%
“…Betting is defined as an inevitable process, escaping individual volition, as a survival process or as a struggle to survive (39). These gendered digital marketing strategies are particularly concerning, as young adult males are the socio-demographic group the most at risk for gambling problems (11). Hing et al showed that impulse betting both before and after match commencement was more frequent among young men, who were clearly the target for sports betting advertising, including promotions for incentivized bets during play (38).…”
Section: A Gendered Marketing Strategymentioning
confidence: 99%
See 2 more Smart Citations